Platelet aggregation: Part II Some results from a new method of study (1962)
The light transmitted through a suspension of platelets increases if the platelets aggregate. A method derived from this observation has been used to study the kinetics of platelet aggregation. Aggregation is more rapid at 37°C., with rapid stirring, with high concentrations of adenosine diphosphate, and a high platelet concentration; a decrease in any of these conditions slows the process.